SAGU : PANGAN LOKAL MASYARAKAT PADA MASA PANDEMI COVID-19 DI KOTA TIDORE KEPULAUAN - Ansar, Hafiz; Pratiknjo, Maria Heny; Sandiah, Nasrun (HOLISTIK, Journal Of Social and Culture, 2021)
The availability of local food Tidore during the coronavirus pandemic (Covid-19) has become a need that many citizens are looking for in an effort to maintain the cultural life of indigenous peoples in eastern Indonesia. Various local foods owned by Tidore nature that has food wealth such as sago, sweet potatoes, taro, cassava (kasbi) and various types of vegetables are the most reliable daily staples of the citizens.During the Covid-19 Pandemic there were symptoms that the shift in consumption of staple foods again switched from rice to sago caused by the food crisis, especially rice followed by the implementation of a policy of restricting access in and out of an area. The lack of rice imports that occurred during the Covid-19 pandemic made many people switch to eating sago which culturally has been a staple food for a long time in the islands of Tidore City. This makes it an increase and becomes an alternative to staple foods during pandemics.Efforts to disinging food to overcome the problem of dependence on one basic food only. For example, by processing yam into various forms that have a special taste and long shelf life. One of the processed forms of yam in North Maluku is cassava starch (sagu kasbi) or sago cake (sagu lempeng) model derived from cassava.Keywords: Sago, food, pandemic covid-19